SELF-CONTROL GROUP COUNSELING REDUCES SOCIAL MEDIA ADDICTION IN EARLY ADOLESCENTS - Bennedicta Cahya; Wiwik Kusdaryani; Eka Sari Setianingsih (CV. TOTUS TUUS, 2026)
Problematic social media use can disrupt adolescents’ learning, direct social interaction, and emotional regulation, yet evidence concerning brief school-based counseling responses remains limited. This study examined whether group counseling incorporating self-control techniques reduced social media addiction among eighth-grade students. A quantitative pre-experimental one-group pretest-posttest design was used. From a population of 256 students, 10 students with high pretest scores were selected purposively. Participants completed a four-response Likert-style social media addiction scale before and after six counseling sessions. Descriptive statistics, Shapiro-Wilk tests, and a paired-samples t-test were applied. The mean score decreased from 107.5 to 85.0, representing a 22.5-point or 20.9% reduction. The paired comparison was statistically significant, t(9) = 6.945, p < .001; a supplementary effect-size calculation based on the reported test statistic indicated a very large within-participant effect (Cohen’s dz = 2.20). These findings suggest that structured group counseling may strengthen adolescents’ capacity to monitor urges, regulate access, schedule alternative activities, and use social media more adaptively. School counselors may use the intervention as a targeted early-response strategy, while avoiding the assumption that all intensive use is pathological. Future research should employ randomized or controlled designs, larger multisite samples, follow-up measurement, objective usage indicators, and fully reported instrument validity, reliability, and ethical approval information.